Stabilization of premixed flame behavior using time-variable-angle swirl vanes - Masaharu KOMIYAMA; Yusuke MIZUNO; Satoshi NISHIDA (Nihon Kikai Gakkai ronbunshu, 2023)
In this study, we aimed to stabilize premixed flame behaviors in a circular pipe with swirling flow. We constructed a system that automatically changes swirl vane angles according to the flame tip positions keeping the air ratio and flow rate. In addition, we tried to stabilize the flame behavior using this system, and simultaneously employed time-series PIV measurements in the flow fields in the circular pipe. The findings obtained in this study are shown below. (1) Under this experimental condition, it was shown that there was a positive and strong correlation between the flame tip positions and the integrated scattering intensity of tracer particles in a circular pipe with swirling flow. (2) Using the integrated scattering intensity of tracer particles as an index, the change of the flame tip positions was judged, and the swirl vane angle could be changed according to the behavior of the premixed flame. It was shown that keeping the flame tip positions within the circular pipe was possible. (3) While operating the flame position stabilization system, time-series PIV measurements simultaneously measured the flow fields near the flame tip. From the results, when the swirl vane angle was changed in the positive direction, an upstream-direction velocity region appeared by increasing the swirl intensity. After that, the flame propagated upstream along the formed upstream-direction velocity region.